Los juegos recreativo y su influencia en el desarrollo de las habilidades psicomotrices en los niños del centro educativo Felipe Borja de la parroquia San Carlos del cantón Quevedo - Ube Lara, Luis Alexander (2018)
This project focuses on recreational games and their influence on the development of psychomotor skills in the children of the "Felipe Borja" Educational Center of San Carlos Parish. The recreational games are born with the purpose of helping the student with the freedom to use their imagination creating well-established academic patterns establish a bond of cooperation working as a team, promote imagination and bonds of friendship with well-founded values. With the research carried out, it could be noted the lack of activities that help to develop the gross psychomotor skills, that is why a manual of recreational activities was elaborated that contributes to the development of the psychomotor abilities of the students. It is expected that by means of the proposal the academic objectives of the Enrique Borja educational center can be achieved, the infants in this stage require special attention to their student start and the knowledge they acquire throughout the academic process is fundamental for their intellectual development , it is necessary that the teacher has the necessary instructions on the pedagogical strategies that can be applied when these types of difficulties arise, evaluating the causes, effects, and if they are yielding the expected results